S-ketamine facilitates motor function recovery after brachial plexus root avulsion and reimplantation in mice - Ronghua Huang; Ronghua Huang; Bingbiao Lin; Lingtai Yu; Lingtai Yu; Qichen Luo; Hongyan Tian; Chenrui Li; Naili Wei; Shaohui Zhuang; Jian Chen; Yalan Li; et al. (Frontiers in Pharmacology)
BackgroundBrachial plexus root avulsion (BPRA) often occurs in high-speed traffic accidents or shoulder dystocia, resulting in motor dysfunction. S-ketamine, a clinical anesthetic and antidepressant drug, is an NMDA receptor antagonist that may be effective against glutamate excitotoxicity after nerve injury. Therefore, we aimed to elucidate the potential effectiveness of S-ketamine on motor function recovery after BPRA in mice.MethodsA mouse model of BPRA and reimplantation was established, and mice were randomly assigned to either the S-ketamine group or the control group, receiving a low, subanesthetic dose of S-ketamine or normal saline, respectively. The restoration of the motor neural circuit—from spinal cord and myocutaneous nerve to biceps muscle—was evaluated. Fluoro-Gold retrograde tracing was utilized to assess the connectivity between the central and peripheral nerve systems. Behavioral tests such as CatWalk, grooming test, and grip strength were applied to assess motor function recovery. The underlying mechanism was analyzed by Western blot, and the rescue experiment was assessed via motor function behavioral tests.ResultsS-ketamine increased motor neuron survival, enhanced central and peripheral nervous connectivity, promoted axon regeneration and remyelination, improved the neuromuscular junction integrity, and prevented muscle atrophy. As a result, motor function recovery was significantly improved, which was attributed to increased BDNF production via ERK-CREB phosphorylation. The BDNF receptor antagonist, ANA12, counteracted the functional recovery induced by S-ketamine.ConclusionS-ketamine increases the BDNF concentration by ERK/CREB phosphorylation, thereby promoting motor neural circuit repair and facilitating motor function recovery.